Companion to continental philosophy / edited by Simon Critchley and Willam R. Schroeder - "Critchley, Simon (ed.)" (Oxford, 2000)
Covering the complete development of post-Kantian Continental philosophy, this volume serves as an essential reference work for philosophers and those engaged in the many disciplines that are integrally related to Continental and European Philosophy.
Keywords: "Philosophy, oriental"